Measurement of Collins asymmetries in inclusive production of charged pion pairs in e+e- annihilation at BABAR - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
We present measurements of Collins asymmetries in the inclusive process e+e−→ππX, where π stands for charged pions, at a center-of-mass energy of 10.6 GeV. We use a data sample of 468 fb−1 collected by the BABAR experiment at the PEP-II B factory at SLAC, and consider pairs of charged pions produced in opposite hemispheres of hadronic events. We observe clear asymmetries in the distributions of the azimuthal angles in two distinct reference frames. We study the dependence of the asymmetry on several kinematic variables, finding that it increases with increasing pion momentum and momentum transverse to the analysis axis, and with increasing angle between the thrust and beam axis.
Die Zeichen + und - in e+e- im Titel sind hochgestellt, das e ist kursiv geschrieben
Published 9 September 2014
Gesehen am 03.09.2020